Noncontact Intraocular Pressure Measurement over Bandage Contact Lens and the Effect of Pentacam and Corvis ST’s IOP Correction System - Xueting Cai; Yi Qin; Sixiu Liu; Zhewei Cheng; Fan Lu; Jia Qu; Ding Chen (Journal of Ophthalmology)
Purpose. To evaluate the influence of intraocular pressure (IOP) measurement while wearing bandage contact lens (BCL) and the effect of Pentacam and Corvis ST’s correction systems. Methods. It was a prospective comparative study. Forty healthy subjects (40 eyes) were included in this study. Eyes were measured using noncontact tonometer (NCT), Corvis ST, and Pentacam before and after wearing BCL. Pentacam’s five correction formulas (Ehlers formula, Shah formula, Dresden formula, Kohlhaas formula, Orssengo/Pye formula) and Corvis ST’s correction formulas (Ehlers formula and biomechanical corrected formula) were used to correct the IOP values before and after BCL wearing. The IOP values were compared, and the correction effect of different systems were evaluated. Results. The mean age of the subjects was 24.4 ± 0.60 years. The mean IOP obtained by NCT was 14.8 ± 3.2 mmHg before BCL wearing and was 15.7 ± 3.4 mmHg after BCL wearing. The mean IOP was significantly increased after BCL wearing (0.9 ± 2.9 mmHg, P=0.05). Four of the five Pentacam’s correction formulas (except Kohlhaas formula) showed no significant difference in the mean corrected IOP values before and after BCL wearing (all P>0.05). The mean IOP obtained by Corvis ST was 13.7 ± 2.8 mmHg before BCL wearing and was 15.0 ± 4.0 mmHg after BCL wearing. The mean IOP was significantly increased after BCL wearing (1.3 ± 2.4 mmHg, P<0.05). Corvis ST’s correction formula (Ehlers formula other than biomechanical corrected formula) showed no significant difference in the mean corrected IOP values before and after BCL wearing (P>0.05). Conclusion. The IOP measurements over BCL by NCT and Corvis ST was found to be increased. The correction systems of Pentacam (Ehlers formula, Shah formula, Dresden formula, and Orssengo/Pye formula) and Corvis ST (Ehlers formula) are useful in correcting the IOP measuring deviation induced by BCL wearing.